How Man Seized Fire (Symphony in the Flint Hills, 2015)
An Australian Aboriginal folklore. Long ago the animals that now live in the bush were men. A tribe returning from a hunt encountered a very old man who told them a story of how man seized fire.
Keywords: tribal; story; Aboriginal; Folklore; fire; animals; man; Australian; Kookaburra; desert; cockatoo